Castro de Monte Mozinho: Cerâmicas de Paredes Finas - Soeiro, Teresa; Morais, Rui (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
In this paper we present the thin-walled ware found in Castro de Monte Mozinho, in the excavations campaigns dated from 1974 to 1998. We identify all the sectors covered by the work and we sum up the stratigraphic contexts in which the findings of the thin-walled ware occurred, highlighting their relation to other contemporary materials. We then present the productions according to their type and fabric, having been able to identify two distinct ones. On the one hand, we verified the existence of Italic thin-walled ware manufactured both in the Central North region (Etruscan coast) and in the Central Western area of the Po Valley and, on the other hand, and in a more significant number, we recognised peninsular productions from the Baetica and Lusitania, with emphasis to the ones produced in Mérida.